Linking Perceived Organizational Support and Ethical Leadership to Employee Wellbeing: The Mediating Role of Job Crafting - Darmilisani Darmilisani; Saimara A. M. Sebayang (Yayasan Sinergi Kawula Muda, 2026)
This study examines how perceived organizational support and ethical leadership influence employee wellbeing in foreign-invested plantation organizations, addressing a gap in the literature regarding the distinct roles of behavioral and attitudinal mediators in labor-intensive contexts. While prior studies often position job crafting and work engagement as complementary mechanisms, this study explicitly compares their mediating roles within a single framework. Using a quantitative design, data were collected from 170 employees out of a population of 258 through a census-based approach and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived organizational support (β = 0.290, p < 0.05) and ethical leadership (β = 0.372, p < 0.05) have significant positive effects on employee wellbeing. Job crafting also has a significant positive effect on wellbeing and significantly mediates the relationships between perceived organizational support and wellbeing as well as between ethical leadership and wellbeing (p < 0.05). In contrast, work engagement does not have a significant direct or mediating effect (p > 0.05). These findings emphasize job crafting as the key empirically supported mechanism linking organizational support and ethical leadership to employee wellbeing, highlighting the importance of proactive work behaviors over attitudinal states in plantation settings. This study contributes to the literature by clarifying the differential roles of mediators and provides practical implications for designing interventions that foster employee-initiated job redesign to enhance wellbeing in labor-intensive industries.